Long-term survival and post-hoc analysis of toripalimab plus definitive chemoradiotherapy for oesophageal squamous cell carcinoma: insights from the EC-CRT-001 phase II trialResearch in context - Ruixi Wang; Yihong Ling; Baoqing Chen; Yujia Zhu; Yonghong Hu; Mengzhong Liu; Yadi Yang; Li Zhang; Yingxin Lv; Shiliang Liu; Qiaoqiao Li; Mian Xi (EClinicalMedicine, 2024)
Summary: Background: In the EC-CRT-001 phase II study, the combination of toripalimab (an anti-programmed death-1 antibody) and definitive chemoradiotherapy (CRT) has shown promising efficacy in patients with locally advanced oesophageal squamous cell carcinoma (ESCC). Here, we reported the long-term outcomes and post-hoc exploratory analyses. Methods: This single-arm, phase II trial enrolled 42 patients diagnosed with unresectable stage I–IVA ESCC was conducted at Sun Yat-sen University Cancer Center between November 2019 and January 2021. Treatment consisted of chemotherapy (weekly 50 mg/m2 of paclitaxel and 25 mg/m2 of cisplatin for five cycles), concurrent radiotherapy (50.4 Gy in 28 fractions), and toripalimab (240 mg every 3 weeks for up to 1 year). The primary endpoint was clinical complete response (CR) rate at 3 months after CRT completion. The 3-year overall survival (OS) and progression-free survival (PFS) rates were evaluated. Additionally, the exploratory objectives included analysing recurrence patterns, assessing the associations between immune-related adverse events (irAEs) and efficacy, and identifying potential predictors for irAEs. The trial was registered with ClinicalTrials.gov (NCT04005170). Findings: With a median follow-up of 44.3 months (IQR 40.8–46.1), the 3-year OS and PFS rates were 44.8% (95% CI 31.9–62.8) and 35.7% (95% CI 23.8–53.6), respectively. Patients who failed to achieve a clinical complete response (CR) demonstrated significantly worse OS (hazard ratio [HR] = 13.73, 95% CI 4.43–42.54, P < 0.0001) and PFS (HR = 32.08, 95% CI 8.57–120.10, P < 0.0001). Disease recurrence occurred in 23 of 42 patients (55%), with recurrences being earlier and more frequent in the non-CR group compared to the CR group. Patients experiencing irAEs showed a significantly higher CR rate (72% vs. 39%, P = 0.082) and better PFS (HR = 0.43, 95% CI 0.19–0.93, P = 0.027) than those without irAEs. GON4L mutation was associated with a lower incidence of irAEs (P = 0.036). Interpretation: The updated survival outcomes confirmed the efficacy of toripalimab plus definitive CRT in locally advanced ESCC. Moreover, the development of irAEs may predict a more favourable prognosis. Funding: National Natural Science Foundation of China, Beijing Xisike Clinical Oncology Research Foundation, and Sci-Tech Project Foundation of Guangzhou.